Students' perceptions on teaching quality determinants: A study in the Northern Region universities - Said, Roshima; Wan Omar, Maznah; Hussin, Zaliha; Awang, Norasmila (2004)
This paper examines and analyzed the perceptions towards teaching quality determinants among Public University students in the Northern Region of Peninsular Malaysia. Questionnaires surveys were directed to a total of 500 students from 3 Public Universities which includes UiTM Kedah, UiTM Perlis, UiTM Penang, Universiti Utara Malaysia and Universiti Sains Malaysia. 17 teaching quality determinant factors were identified in this study which was added to the original study done by Broder and Dorfman (1994). Determinants include Clarity, Feedback, Syllabus, Creativity, Practicality, Exercises, Attention, Enthusiasm, Availability, Approachable, Communication, Language Use, Extra Reading, Technology, Punctuality, Motivation and Current Issue. The result shows that clarity is the most important determinant in determining teaching quality among lecturers. The research result may provide some feedback for the development of teaching quality in universities towards world class status.